Evaluation Report on the Integrated Child Development Services Projects (1976-78) - Planning Commission (Planning Commission, 1982)
The Integrated Child Development Services (1CDS) Scheme, launched by the Government of India on October 2, 1975 had the specific objective of improving the nutritional and health status of children in the age group of 0—5-iycars and to reduce the incidence of mortality, morbidity, mal-nutrition and school drop-out, besides enhancing the capability of the mother to look after the normal health and nutritional needs of the child. With this end in view, the Scheme was included in the Fifth Five Year Plan (1974-79) with a total outlay of Rs. 7.40 crores.
Programme Evaluation Organisation Planning Commission Government of India New Delhi